Heat Production Measurement of Activated Sludge by Calorimetry - Genc, Nevim (Array, 2008)
Summary: Microbial heat generation (Qf ) is an important parameter to control a biological process. Qf can be determined by various methods. In this study, a system for online calorimetric measurements for activated sludge is developed: a pilot scale bioreactor of 100 L volume as a calorimeter. The calorimetric measurements were calibrated using the heat production of Saccharomyces cerevisiae consuming glucose so that Qf can also be measured using the relation of oxygen transfer rate OTR and the combustion enthalpy of glucose ( cH0) (Q H f c 0 OTR). Next, the Qf of activated sludge with glucose as substrate is measured using the verified experimental set. A constant value for OTR to calculate Qf could not be detected because the activated sludge comprises a mixture of organic and unknown substrates and a heterogeneous flora of microorganisms. Heat energy production decreased during the experiment, pointing to a declining of microbial activity due to endogenous oxidation of the sludge